2016
DOI: 10.1111/dmcn.13328
|View full text |Cite
|
Sign up to set email alerts
|

Change in pain status in children with cerebral palsy

Abstract: Children with CP with more severe initial pain and higher gross motor function have lower pain at follow-up indicating an improvement in pain status over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 30 publications
(81 reference statements)
3
40
1
Order By: Relevance
“…Experience of pain may change over time as may intensity . Those who at a younger age have no pain may develop it, and those with more severe initial pain and higher gross motor function have lower pain at follow‐up . Also relevant to prevalence is who is reporting the pain: self‐report or physician observer (54% vs 39% respectively) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experience of pain may change over time as may intensity . Those who at a younger age have no pain may develop it, and those with more severe initial pain and higher gross motor function have lower pain at follow‐up . Also relevant to prevalence is who is reporting the pain: self‐report or physician observer (54% vs 39% respectively) .…”
mentioning
confidence: 99%
“…Ascertaining pain in the non‐verbal population is more problematical as pain has to be inferred from behaviour and relies on parent/carer/observer report. High agreement was reported between physiotherapist and parents in non‐verbal children . Which pain questionnaire to use has varied across studies; a systematic review concluded that tools were often not validated in children with CP, nor was there one tool to meet the needs of all children experiencing chronic pain …”
mentioning
confidence: 99%
“…correctly highlight, minimal evidence is available on best practices for clinicians to manage pain in individuals with CP. The field also lacks an understanding of pain trajectories over time, although there is some evidence of the existence of chronic pain . Researchers need to continue to build this evidence base and evaluate mechanisms to support chronic pain management.…”
mentioning
confidence: 81%
“…A year ago, Kjersti Ramstad wrote a commentary on a cross‐sectional study on pain published in DMCN titled ‘Pain hurts worldwide: non‐verbal children with cerebral palsy’ . The present study by Christensen et al is a follow‐up. Indeed, though research on pain in cerebral palsy (CP) has been performed over the last two decades, longitudinal studies are lacking.…”
mentioning
confidence: 88%